2019
DOI: 10.1016/j.surg.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Serum FABP4 concentrations decrease after Roux-en-Y gastric bypass but not after intensive medical management

Abstract: Background: Serum concentrations of fatty acid binding proteins 4 (FABP4), an adipose tissue fatty acid chaperone, have been correlated with insulin resistance and cardiovascular risk factors. The objective of this study are to: (1) To assess relationships between Roux-en-Y gastric bypass (RYGB), intensive lifestyle modification and medical management protocol (LS/IMM), FABP4, and metabolic parameters in obese patients with severe type 2 diabetes mellitus (T2DM). (2) To evaluate the relative contribution of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In humans, serum levels of FABP4 are higher in obese, type 1 diabetic, type 2 diabetic and gestational diabetic individuals compared to non-obese, non-diabetic subjects [ 34 , 35 , 36 , 37 ]. Gastric bypass surgery reduces circulating FABP4 by 42% in obese patients with type 2 diabetes, whereas behavioral and nutritional intervention alone does not reduce the serum levels of FABP4 [ 35 ].…”
Section: Fabp4mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, serum levels of FABP4 are higher in obese, type 1 diabetic, type 2 diabetic and gestational diabetic individuals compared to non-obese, non-diabetic subjects [ 34 , 35 , 36 , 37 ]. Gastric bypass surgery reduces circulating FABP4 by 42% in obese patients with type 2 diabetes, whereas behavioral and nutritional intervention alone does not reduce the serum levels of FABP4 [ 35 ].…”
Section: Fabp4mentioning
confidence: 99%
“…In humans, serum levels of FABP4 are higher in obese, type 1 diabetic, type 2 diabetic and gestational diabetic individuals compared to non-obese, non-diabetic subjects [ 34 , 35 , 36 , 37 ]. Gastric bypass surgery reduces circulating FABP4 by 42% in obese patients with type 2 diabetes, whereas behavioral and nutritional intervention alone does not reduce the serum levels of FABP4 [ 35 ]. Cohort studies including obese or diabetic patients with their family revealed that FABP4 levels were high with first-degree relatives of type 1 diabetic patients [ 37 ] and in children of obese parents, even if they were not obese themselves [ 38 ].…”
Section: Fabp4mentioning
confidence: 99%